The severity prediction of the binary and multi-class cardiovascular disease − A machine learning-based fusion approach. (June 2022) - Kibria, Hafsa Binte; Matin, Abdul
Abstract: In today's world, a massive amount of data is available in almost every sector. This data has become an asset as we can use this enormous amount of data to find information. Mainly health care industry contains many data consisting of patient and disease-related information. By using the machine learning technique, we can look for hidden data patterns to predict various diseases. Recently CVDs, or cardiovascular disease, have become a leading cause of death around the world. The number of death due to CVDs is frightening. That is why many researchers are trying their best to design a predictive model that can save many lives using the data mining model. In this research, some fusion models have been constructed to diagnose CVDs along with its severity. Machine learning(ML) algorithms like artificial neural network, SVM, logistic regression, decision tree, random forest, and AdaBoost have been applied to the heart disease dataset to predict disease. Randomoversampler only for multi-class classification to make the imbalanced dataset balanced. To improve the performance of classification, a weighted score fusion approach was taken. At first, the models were trained. After training, two algorithms' decision was combined using a weighted sum rule. A total of three fusion models have been developed from the six ML algorithms. The results were promising in the performance parameter. The proposed approach has been experimented with different test training ratios for binary and multiclass classification problems, and for both of them, the fusion models performed well. The highest accuracy for multiclass classification was found as 75%, and it was 95% for binary. Graphical Abstract: ga1 Highlights: Three weighted score-based fusion models to predict the severity of Cardiovascular disease. Application of machine learning in health care for Cardiovascular disease prediction. Binary and multi-class classification of patients with and without Cardiovascular disease. Empirical results of comparisons confirm the proposed fusion model's superiority over single machine learning algorithms.